Quantifying Shoebill (Balaeniceps rex) habitat suitability in the Bangweulu Wetlands, Zambia - Musker, Seth (Department of Biological Sciences, 2014)
A quantitative analysis of suitable habitat for the Shoebill (Balaeniceps rex), a large waterbird confined to African swamps, was conducted by using a combination of aerial photographs and a previously determined habitat suitability model from the Bangweulu Wetlands, Zambia. The Shoebill is considered Vulnerable on the IUCN red list, but there are no pre-existing quantitative data on the composition of suitable habitat for this species. Both univariate and multivariate analyses revealed that non-wetland habitats as well as non-vegetated wetland habitats have low suitability compared to vegetated wetland habitats. Notably, reeds correlated significantly and positively with suitability (rs = 0.338, p < 0.001). We found little support for the hypothesis that floating vegetation is highly suitable for Shoebills, but the analysis for this habitat may have suffered as a result of confounding factors. The relationship between flooded grassland and suitability was highly variable and was not significant (rs = 0.009, p = 0.807). In contrast, dry grassland correlated positively with suitability (rs =0.289, p < 0.001), but its suitability scores were generally much lower than for flooded grassland. Quantitative data on Shoebill habitat suitability will be useful for future Shoebill population surveys, and will improve our ability to make informed decisions regarding its conservation.